Potential of Kirinyuh Leaf Extract (Chromolaena odorata L) in Controlling Ajeran Weed (Bidens Pilosa L) and Eleusine Indica L - Darul Zumani; Titi Ayu Wijayanti (Publikasi Indonesia, 2024)
Kirinyuh (Chromolaena odorata L.) It contains tannins, steroids, phenols, and other compounds that can inhibit the growth of other plants around it, so it can be used as a vegetable herbicide. This study aims to determine the concentration of kirinyuh leaf extract that is effective in controlling ajeran weed (Bidens pilosa L.) and bone grass (Eleusine indica L.) research was conducted in the experimental garden of the Faculty of Agriculture, Siliwangi University. This study uses a group random design (RAK) with 5 replicates. The treatment consisted of 0%, 10%, 20%, 30%, and 40% kirinyuh leaf extract concentrations. The results showed that the concentration treatment of kirinyuh leaf extract was effective in suppressing the growth of ajeran weed (Bidens pilosa L.) and bone grass (Eleusine indica L.)